New synonyms and combinations in Eurasian Brassicaceae (Cruciferae) - German, Dmitry (Phytotaxa, 2014)
Taxonomy of miscellaneous taxa of Eurasian Brassicaceae is updated. Eight names at the species rank are reduced for the first time to synonymy of what follows them in parentheses: Cardamine szeewaldiana (C. macrophylla), Hesperis hyrcanica (Clastopus vestitus), Arabis oxyota (Crucihimalaya bursifolia), Hesperis speciosa and Parrya integerrima (Dendroarabis fruticulosa), Cheiranthus taraxacifolius (Erysimum cuspidatum), Draba ishkomania (Scapiarabis saxicola), Velarum tzvelevii (Sisymbrium officinale). Three new combinations (Hormathophylla kuepferiana, Isatis odontogera, and Parrya khorasanica) are proposed, first of them as a replacing name for a later homonym in the genus Hormathophylla. Three names (Arabis oxyota, Clastopus vestitus, and Crucihimalaya bursifolia) are lectotypified (for C. vestitus, a previous choice is narrowed) and a neotype is designated for Isatis odontogera. Nomenclatural comments are provided where needed.
Gesehen am 24.07.2020